Metabolomic analysis of serum using proton NMR in 6-OHDA experimental PD model and patients with PD. (March 2020) - Kumari, Sadhana; Kumaran, S Senthil; Goyal, Vinay; Bose, Samrat; Jain, Suman; Dwivedi, Sada Nand; Srivastava, Achal Kumar; Jagannathan, Naranamangalam R
Graphical abstract: Image 1 Highlights: Identification of biomarkers are essential for the diagnosis and prognosis of PD. Serum metabolomics compared between PD patients and HC; PD model and sham control. Elevated metabolites: 6 in PD patients, 7 in experimental model; 4 common in both. A negative correlation between clinical phenotype and metabolic profile was observed. Impairment in gut microflora system and amino acids metabolism was observed.